2020
DOI: 10.1101/2020.03.03.975557
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Spindle position dictates division site during asymmetric cell division in moss

Abstract: 14Asymmetric cell division (ACD) underlies the development of multicellular organisms. 15The division site in plant cells is predetermined prior to mitosis and the localization of 16 the mitotic spindle is considered static, unlike in animal ACD, where the cell division site 17is defined by active spindle-positioning mechanisms. Here, we isolated a novel mutant of 18 the microtubule-associated protein TPX2 in the moss Physcomitrella patens and observed 19 abnormal spindle motility, which led to inverted asymme… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Live imaging of shoot initials has revealed that the angle of the first three divisions is robust, indicating that division plane establishment is tightly controlled and crucial for phyllotaxis [9,32]. This is also suggested by mutants where apical cell formative divisions are defective and leafy shoot development cannot proceed normally [33], such as Defective Kernel1 (DEK1) [34,35], No Gametophores 1 (NOG1) [18], Targeting Protein for Xklp2 (TPX2) [36] or mutants in the CLAVATA (CLV) signaling pathway [37].…”
Section: Stem Cell Regulators and Microtubules Dictate Division Planementioning
confidence: 99%
See 1 more Smart Citation
“…Live imaging of shoot initials has revealed that the angle of the first three divisions is robust, indicating that division plane establishment is tightly controlled and crucial for phyllotaxis [9,32]. This is also suggested by mutants where apical cell formative divisions are defective and leafy shoot development cannot proceed normally [33], such as Defective Kernel1 (DEK1) [34,35], No Gametophores 1 (NOG1) [18], Targeting Protein for Xklp2 (TPX2) [36] or mutants in the CLAVATA (CLV) signaling pathway [37].…”
Section: Stem Cell Regulators and Microtubules Dictate Division Planementioning
confidence: 99%
“…(B) In WT, following the first division of the shoot initial (i), the apical domain (marked by an asterisk) undergoes a series of oblique divisions (ii-iv) leading to the formation of the tetrahedral apical stem cell (coloured in green) at the origin of spiral phyllotaxis. (A) adapted from[9,36,37], (B) redrawn from[9] with permission from corresponding author.…”
mentioning
confidence: 99%
“…In the study of these processes, the divisions in P. patens protonemata and buds have proven to be experimentally accessible models. For example, recent findings show that the microtubule-associated protein TPX2 is essential for maintenance of a central spindle position along the apical–basal axis in buds [ 62 ]. This defect could surprisingly be compensated by actin cytoskeleton disruption, which, under normal conditions, does not significantly interfere with spindle/phragmoplast positioning [ 21 , 62 ].…”
Section: Role Of the Cytoskeleton In Division Plane Controlmentioning
confidence: 99%
“…For example, recent findings show that the microtubule-associated protein TPX2 is essential for maintenance of a central spindle position along the apical–basal axis in buds [ 62 ]. This defect could surprisingly be compensated by actin cytoskeleton disruption, which, under normal conditions, does not significantly interfere with spindle/phragmoplast positioning [ 21 , 62 ]. These findings open new avenues for study on the mechanisms controlling “tugging” of the division apparatus during mitosis and its implications for division plane positioning.…”
Section: Role Of the Cytoskeleton In Division Plane Controlmentioning
confidence: 99%
“…Size control occurs at one or more checkpointsone that precedes the initiation of DNA synthesis (G1/S transition) and the other before nuclear division (G2/M transition). Critical cell size is obligatory for cell cycle progression and is entirely reliant on habituating conditions (García-Gó mez et al 2020;Kozgunova et al 2020;Winnicki 2020).…”
Section: Introductionmentioning
confidence: 99%